(untitled) (Journal of Contemporary Philology, 2020)
The paper focuses on exploring the intertextual relationship (the hypotext versus the hypertext) between the representation of Dina’s story from the Bible and her representation as the main focalisator/main character in the novel The Red Tent by Anita Diamant. The main focus is set on the possible theoretical explanations between the main text from the Bible (Genesis 34 as hypotext), and how this story is recreated in Diamant’s novel The Red Tent (as a hypertext). Dina, from the Bible is a marginal, voiceless character which is represented through the voices of her brothers, even despite her rape. In the novel by Diamant, she is transformed as the main focalisator (i.e. she is the narrator who tells the story of her rape), which means that the novel The Red Tent represents the story of Dina as Dina herself gives notion to it. However, this paper does not deal with the theories of feminism which are and can be plausible for interpretations of The Red Tent but, instead, it puts the focus on the intertwinement of both of the texts though the theory of intertextual relations (Gérard Gеnette, Ulrich Broich, Umberto Eco).